Rapid In Situ Immobilization of Enzymes in Metal–Organic Framework Supports under Mild Conditions. Issue 7 (2nd March 2017) - Gascón, Victoria; Carucci, Cristina; Jiménez, Mayra B.; Blanco, Rosa M.; Sánchez‐Sánchez, Manuel; Magner, Edmond
Abstract: The use of a metal–organic framework (MOF) as a support for the in situ immobilization of enzymes was explored. The MOF support, a Basolite F300‐like material, was prepared from FeCl3 and the tridentate linker trimesic acid. Immobilization of alcohol dehydrogenase, lipase, and glucose oxidase was performed in situ under mild conditions (aqueous solution, neutral pH, and at room temperature) in a rapid and facile manner with retention of activity for at least 1 week. The catalytic activities of lipase and glucose oxidase were similar to the activities of the free enzymes; with alcohol dehydrogenase, there was a substantial decrease in activity on immobilization that may arise from diffusion limitations. The approach demonstrates that a MOF material, prepared from cheap and commercially available materials, can be successively utilized to prepare stable and catalytically active biocatalysts in a rapid and facile manner. Abstract : Offering support : Enzymes can be immobilized on metal–organic framework (MOF) supports in a rapid and facile manner under mild conditions, and the enzymes retain their catalytic activities.